Using a panel of immunomarkers to define homologies in mammalian brains - Watson, Charles R.; Paxinos, George; Tokuno, Hironobu (Frontiers in Human Neuroscience, 2010)
Brain mapping has relied on a small number of routine chemical stains for many decades. The advent of immunomarkers has had a major impact on the ability to define homologous nuclei from one species to another. The first atlas to present a panel of immunomarkers was that of Paxinos et al. (1999a,b) in the adult rat brain. The markers used were parvalbumin, calbindin, calretinin, SMI32, tyrosine hydroxylase, and NADPH diaphorase (plus nissl and acetylcholinesterase). The ‘signature’ of a nucleus of interest in a new species can be tested against the findings in the rat. Since the pattern of immunomarkers seems to be conserved in mammalian evolution, such extrapolations can be made with reasonable confidence. A marmoset brain stained with a comprehensive set of immunomarkers has recently been published on the internet (Tokuno et al 2009) and we are in the process of defining nuclear homologies in this brain by comparison with the same markers in the rat. In this article, we present an example (mapping the amygdala in the marmoset) which demonstrates the application of this immunomarker panel in defining homologies. The technique is particularly valuable in situations where little data on hodology or electrophysiology are available.